Rola audytu wewnętrznego w kontroli realizacji strategii jednostki samorządu terytorialnego - Filipiak, Beata (Role of Internal Audit in Control of Realization a Local Authority Strategy, 2005)
The article presents problems of audit in local authority. The author discussed practical application in internal audit in public sector, rules, procedures and tasks. There is indicated internal audit as an instrument of control of realization a local authority strategy. The author discussed premises and restrictions to use this instrument.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 147-155